C. S. Peirce on Interpretation and Collateral Experience - Bergman, Mats (Signs - International Journal of Semiotics, 2010)
This article examines C. S. Peirce's conception of collateral experience and its relation to his account of interpretation. The essay proceeds through a general presentation of the two principal phases of Peirce's theory of signs. The key issue of the character of experience is discussed in relation to the problem of the ubiquity of interpretation. The main upshot of the analysis is that the concept of 'collateral experience' is a crucial component in Peirce's mature semeiotic; on the one hand, the collaterality of experience indicates a limit of the semiotic domain, but on the other hand, collateral experience enters into symbolic semiosis as something that needs to be indicated for contextualisation to take place. The article concludes with some reflections on Peirce's ambiguous use of the concept of 'experience'.